The teaching model VaKE in primary education – development and first evaluation: - five projects - five researches (Pedagogical Horizons, 2018)
The teaching model VaKE (Values and Knowledge Education; Patry, 2001) was developed for students at the age of ten and older and has been established there. The Question is, if this is also possible in primary school. The answer should be found as a part of praxis research with five small studies. That would be two dilemmastories without relation to expertise and three VaKE-projekts dealing with protection of nature, dangerous matters and children work.
Keywords: knowledge acquisition, primary school, moral education, constructivism, teaching model